Reframing Stakeholder Salience in Digital Ecosystems: Toward Inclusive Corporate Decision-Making - Alves, Larissa Monteiro Alves; Costa, Rafael Henrique da Costa (ICON Publisher, 2025)
The acceleration of digital transformation has profoundly reshaped stakeholder dynamics, challenging traditional assumptions of stakeholder salience theory. This conceptual paper revisits the classic framework of power, legitimacy, and urgency, proposing a reconceptualisation suited for digital ecosystems. It argues that digitalisation introduces new sources of stakeholder influence, including algorithmic visibility, data control, and network interconnectivity, which redefine salience hierarchies. Drawing upon interdisciplinary perspectives from stakeholder theory, digital governance, and organisational communication, the study develops the notion of digital salience—a dynamic construct reflecting the fluidity of influence in online environments. The paper further explores how inclusive corporate decision-making processes, grounded in transparency and participatory governance, can enhance organisational adaptability and legitimacy in data-driven contexts. The discussion highlights the need for ethical and collaborative frameworks capable of addressing power asymmetries inherent in digital ecosystems. Overall, this research provides theoretical and managerial insights into reframing stakeholder salience for the digital age, bridging classical stakeholder theory with contemporary realities of algorithmic governance and networked stakeholder engagement.